Desafios do conselho escolar na gestão financeira e no fortalecimento da democratização da escola - Lucas, Angelita Fernanda Teixeira (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation aims to analyze the links between the participation of counselors and the implementation of legal norms in financial management, seeking to understand their contributions to strengthening the process of democratization in schools. The empirical field was defined based on the researcher's experience as a school board member and concerns about public policies aimed at democratizing education, with the School Board of School João Belchior Marques Goulart, an Elementary School located in São Leopoldo, Rio Grande do Sul, as the object of study. This choice made it possible to reflect on the legal aspects and experiences of participation in the board. Based on the theoretical context, it was possible to critically discuss the relationships between laws and the concepts of participation attributed to the School Board, as well as the ways in which these materialize in the face of an organizational culture still marked by authoritarian experiences. Historical and legal aspects of resource decentralization policies were considered, in addition to the concepts of autonomy, decentralization, and participation. The research adopted a qualitative approach, using documentary analysis, participant observation, and culture circles as methodological procedures. These instruments made it possible to identify both the potentialities and difficulties related to financial management, recognized as a relevant factor for the council's performance and for the implementation of school democratization. The research data showed that public education policies, including resource decentralization, are essential for school management when they ensure democratic principles, and it is necessary to implement them in the institution's daily routine. In addition, the importance of consolidating current regulations, the links established between councilors and the school, as well as interpersonal relationships in the participation process, was highlighted. Based on this trust, it becomes possible to consolidate more active and co-responsible participation, which effectively contributes to the democratization of the school. As a result, an educational intervention proposal was developed, structured as a permanent training program, with the aim of improving the performance of the School Board in the face of the challenges of financial management and strengthening democracy in schools.
Keywords: Conselho escolar; Gestão financeira escolar; Gestão democrática escolar; School board; Financial management; Participatory democracy; ACCNPQ::Ciências Humanas::Educação